Systematic Account on Two Major Soil Macrofauna, Scorpions (Arachnida: Scorpiones) and Centipedes (Chilopoda: Scolopendromorpha) of Chinnar Wildlife Sanctuary, Kerala, India - Aswathi, K.; Balan, Dhanya; Sureshan, P. M. (Indian Forester, 2017)
The present study highlighted the diversity of two important soil macro fauna viz., Centipedes (Chilopoda: Scolopendromorpha) and Scorpions (Arachnida: Scorpiones) from Chinnar Wildlife Sanctuary, Idukki District, Kerala, the Southern Western Ghats. Being a rain shadow area, the study area possesses a unique faunal component. We reported 6 species of Scorpions and 7 species of Scolopendrid centipedes from the study area. The study included the first report of the centipede species Cormocephalus westwoodi westwoodi (Newport) from Kerala and the listing out of Cormocephalus (Dekanonyx) nigrificatus Verhoeff (endemic to Southern India) and Otostigmus gravely (Jangi and Dass) (Endemic to Kerala) and Rhysida lithobiodes trispinosus Jangi and Dass (endemic to Deccan plateau).